2014
DOI: 10.1038/clpt.2014.174
|View full text |Cite
|
Sign up to set email alerts
|

Serendipity and the Discovery of Novel Compounds That Restore Mitochondrial Plasticity

Abstract: The mitochondrial electron transport chain (ETC) plays a central role in energy generation in the cell. Mitochondrial dysfunctions diminish adenosine triphosphate (ATP) production and result in insufficient energy to maintain cell function. As energy output declines, the most energetic tissues are preferentially affected. To satisfy cellular energy demands, the mitochondrial ETC needs to be able to elevate its capacity to produce ATP at times of increased metabolic demand or decreased fuel supply. This mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
153
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 79 publications
(204 reference statements)
1
153
0
1
Order By: Relevance
“…For example, lipid permeable, positively charged antioxidant agents, which are attracted to the negative membrane potential of the mitochondria, have been shown to protect the brain against anoxic, ischemic, hypertensive, and chemical injury (14,39,67,128,136). In addition, cardiolipin-directed compounds have promise as therapeutic agents to protect and restore mitochondrial bioenergics and morphology (139). With the current focus on targeting mitochondria, especially in cancer biology, it seems likely that additional approaches will be examined in the future.…”
Section: Role Of Mitochondria In Cellular Protectionmentioning
confidence: 99%
“…For example, lipid permeable, positively charged antioxidant agents, which are attracted to the negative membrane potential of the mitochondria, have been shown to protect the brain against anoxic, ischemic, hypertensive, and chemical injury (14,39,67,128,136). In addition, cardiolipin-directed compounds have promise as therapeutic agents to protect and restore mitochondrial bioenergics and morphology (139). With the current focus on targeting mitochondria, especially in cancer biology, it seems likely that additional approaches will be examined in the future.…”
Section: Role Of Mitochondria In Cellular Protectionmentioning
confidence: 99%
“…Discovered by serendipity [14], the SS peptides arguably show the greatest promise for AKI at present. In a series of studies in rodent models by Szeto et al [13,15 && ], it has been shown that two agents in this class (SS-20 and SS-31) offer significant protection in AKI because of IRI, with striking positive effects on mitochondrial morphology and function, cell polarity, and overall kidney function.…”
Section: Key Pointsmentioning
confidence: 99%
“…Cyclosporine A, an immunosuppressive drug that protects cells from cell death caused by opening of the mitochondrial permeability transition pore, is being open-label-trialed in Leber's hereditary optic neuropathy, a mitochondrial disease that affects the basal retinal ganglia -hopefully reducing cell death in the retinal ganglion cell layer of the eye. Bendavia is a peptide that prevents cardiolipin from converting cytochrome c into a peroxidase but leaves its electron chain function intact [ 160 ] and is also proposed to improve electron chain effi ciency by improving coupling by reducing proton leak. Also, based upon the preclinical data presented earlier and the fact that it has been used extensively in humans already, a trial using bezafi brate in mitochondrial myopathy caused by mutation in It is interesting to note that six of the seven entities being tested are essentially repurposing or expanded indication approaches.…”
Section: Clinical Approachesmentioning
confidence: 99%